Avaliação da modalidade Compra Institucional da Política de Aquisição de Alimentos da Agricultura Familiar no Instituto Federal do Ceará - Soares, Kamyle Braga (2020)
The Family Farming Food Acquisition Program (EAP) began in 2003 with the advent of Law No. 10,696. At the Federal Institute of Science and Technology of Ceará (IFCE), the mandatory application of 30% in Institutional Purchasing (CI), established by this policy, came with Decree No. 8.974 / 2015. The Campi Fortaleza and Acaraú constitute the research object of this dissertation that evaluated the implementation of this public policy in the units, critically discussing the format of family farming food purchases adopted and considering what the basic documents, socioeconomic circumstances and reality advocate. IFCE and how family farmers understand the EAP. For this, a qualitative research approach was applied, starting from the methodological approach of Depth Assessment, which analyzes four dimensions: a) content analysis; b) context analysis; c) institutional trajectory analysis and d) temporal and territorial spectrum analysis. Through bibliographic, documentary research, participant observation and interviews with IFCE managers and family farmers, it was possible to understand the context and institutional trajectory in which the Policy was formed, also understanding that PAA-CI seeks to open The institutional market for the commercialization of family farming products expands the market and guarantees the farmer's permanence in the field by allowing the sale of production at fairer prices. Having as theoretical reference authors who critically discuss the commercialization and production structures of Brazilian agriculture, it appears that the PAA means an attempt to break the commercialization structures. This discussion is still current, as difficulties persist in the flow of production of small farmers at fair prices, without intermediaries - this being one of the main bottlenecks in the agricultural production chains. The research points out that State interference is important in market correction as a way of repairing this unequal process. It is therefore necessary to discuss the implementation of this program in the IFCE units, given that the success of this Policy depends on the articulation of managers, farmers, cooperatives and associations, and certain difficulties persist in the effectiveness of the program.